INCLUSIVE ISLAMIC RELIGIOUS EDUCATION IN VOCATIONAL SECONDARY SCHOOLS: EXPLORING ADAPTIVE PEDAGOGY, PEER TUTORING, AND ASSESSMENT FOR STUDENTS WITH SPECIAL EDUCATIONAL NEEDS - mu'aiqin azmi; Erlan Muliadi; Azhar (Universitas Islam Negeri Mataram, 2026)
This study explores the implementation of Islamic Religious Education (IRE) in an inclusive vocational school, focusing on learning adaptations, peer tutoring, and assessment practices for students with special educational needs at SMKN 5 Mataram, Indonesia. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis involving IRE teachers, special education teachers, and students. Data were analyzed using thematic analysis. The findings reveal that inclusive IRE learning is facilitated through adaptive instructional planning, multimedia-based teaching strategies, peer tutoring, and flexible assessment practices tailored to students’ diverse learning needs. However, challenges remain, including limited teacher preparation, insufficient individualized learning programs, and inadequate support services. The study highlights the importance of collaborative and adaptive pedagogical approaches in promoting meaningful participation and equitable learning opportunities for students with special educational needs in Islamic education settings.